Врачебный контроль при занятиях подводным спортом - Аскеров Али Асланович (Медицина, 1971)
Экземпляры: КХ (20120514) / Инвентарный номер: 532336 / Цена: 1.64 / Сис.шифр: 61 / Авт.знак: А 90 / ГРНТИ: 77 / ББК: 75.717.91